2020
DOI: 10.1007/jhep09(2020)181
|View full text |Cite
|
Sign up to set email alerts
|

Collinear expansion for color singlet cross sections

Abstract: We demonstrate how to efficiently expand cross sections for color-singlet production at hadron colliders around the kinematic limit of all final state radiation being collinear to one of the incoming hadrons. This expansion is systematically improvable and applicable to a large class of physical observables. We demonstrate the viability of this technique by obtaining the first two terms in the collinear expansion of the rapidity distribution of the gluon fusion Higgs boson production cross section at next-to-n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 235 publications
1
59
0
Order By: Relevance
“…Recently a first step towards N 3 LO TMD distributions have been achieved in [47] by calculating the unpolarized quark TMD PDFs, extending and significantly improving upon the methods in [26,27]. Subsequently, both unpolarized quark and gluon TMD PDFs are obtained in [48], based on an independent method from [49]. In this paper we continue our calculation in [47], and present the N 3 LO results for unpolarized quark TMD FFs, and unpolarized gluon TMD PDFs and FFs.…”
Section: Introductionmentioning
confidence: 87%
“…Recently a first step towards N 3 LO TMD distributions have been achieved in [47] by calculating the unpolarized quark TMD PDFs, extending and significantly improving upon the methods in [26,27]. Subsequently, both unpolarized quark and gluon TMD PDFs are obtained in [48], based on an independent method from [49]. In this paper we continue our calculation in [47], and present the N 3 LO results for unpolarized quark TMD FFs, and unpolarized gluon TMD PDFs and FFs.…”
Section: Introductionmentioning
confidence: 87%
“…In particular, in ref. [62] we showed that the corresponding partonic coefficient function is given by…”
Section: Crossing From Production To Dis Cross Sectionsmentioning
confidence: 99%
“…In this section we briefly review the method introduced in ref. [62] to expand cross sections in the kinematic limit where all final-state radiation becomes collinear to the parton with momentum p 1 or p 2 . In order to illustrate this, it is instructive to decompose the momentum k into its components along these directions,…”
Section: Collinear Limit Of Partonic Coefficient Functionsmentioning
confidence: 99%
See 2 more Smart Citations